Development Of Functions And Role Of House Head In Infection Prevention And Control In Porsea Hospital - Dosmaida Nababan; Tumpal Manurung; Lestari Hutahaean (International Journal of Health Engineering and Technology, 2025)
Head nurse should know all the implementation activities of prevention and control of infection in the ward, but in fact the head nurse still performs the function and role in PPI. This article aims to determine the function and role of head nurse in the prevention and control of infections in Porsea Hospital. The method used was a case study and literature study. The results of the assessment and analysis using SWOT analysis known that PPI team, role in the implementation of the PPI. The function and role head nurse less needed in the implementation of PPI. Head nurse is less involved and considered less influential and was not part in the implementation of PPI. Results of literature studies demonstrate the role of the nurse as chief of staff rooms in the ward who do nursing care to patients are very likely to increase the success of infection control. There has been no direct reference that explains the function and role head nurse in the PPI. Recommendations to the hospital nursing manager in order to increase the head nurse function as a leading manager in the ward through policy support and facilities to support such efforts.